Educational practices for families of children and adolescents using a permanent venous catheter - Verônica Braga Corrêa; Michelle Darezzo Rodrigues Nunes; Ana Luiza Dorneles da Silveira; Liliane Faria da Silva; Selma Petra Chaves Sá; Fernanda Garcia Bezerra Góes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify, in the scientific literature, the educational practices performed by nurses with the families of children and adolescents using long-term venous catheters, concerning home care. Methods: integrative review in LILACS, PubMed, SCOPUS, Web of Science and CINAHL databases, from August to September 2018. Results: we analyzed eight articles that met the inclusion criteria. The results showed that all studies are international, mostly North American and with low level of evidence. The educational practices found were home visits, production of printed educational materials, use of mannequins for simulation, creation of an educational video, and combined educational practices. Final Considerations: the care provided by families at home in the countries studied is more complex than in Brazil, and the conclusion is that Brazilian studies need to advance in publications related to this area.